2012
DOI: 10.1152/ajpregu.00266.2011
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 influences the excitability of neurons in the nucleus of the solitary tract and regulates cardiovascular function

Abstract: Nesfatin-1 has been identified as one of the most potent centrally acting anorexigenic peptides, and it has also been shown to play important roles in the control of cardiovascular function. In situ hybridization and immunohistochemical studies have revealed the expression of nesfatin-1 throughout the brain and, in particular, in the medullary autonomic gateway known as the nucleus of the solitary tract (NTS). The present study was thus undertaken to explore the cellular correlates and functional roles of nesf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 29 publications
2
31
0
1
Order By: Relevance
“…Infected neurons were also identified at other sites within the hypothalamus and extrahypothalamic nuclei (24)(25)(26)(27). Nesfatin-1 administration into the nucleus of the solitary tract, a pseudorabies virus-positive area, elevated BP and HR (28), suggesting that an extrahypothalamic area may be responsible for central nesfatin-1 activity within the brain stem. Therefore, additional investigations are required to elucidate the role of the PVN and/or other nuclei in mediating the sympathetic nerve response evoked by nesfatin-1.…”
Section: Diabetesdiabetesjournalsorg Tanida and Associatesmentioning
confidence: 95%
“…Infected neurons were also identified at other sites within the hypothalamus and extrahypothalamic nuclei (24)(25)(26)(27). Nesfatin-1 administration into the nucleus of the solitary tract, a pseudorabies virus-positive area, elevated BP and HR (28), suggesting that an extrahypothalamic area may be responsible for central nesfatin-1 activity within the brain stem. Therefore, additional investigations are required to elucidate the role of the PVN and/or other nuclei in mediating the sympathetic nerve response evoked by nesfatin-1.…”
Section: Diabetesdiabetesjournalsorg Tanida and Associatesmentioning
confidence: 95%
“…Nucb2 mRNA and NUCB2/nesfatin-1 protein expression was observed in this nucleus (Brailoiu et al 2007, Foo et al 2008 and both central nervous and peripheral administration of nesfatin-1 induce c-fos expression in its neurons (Maejima et al 2009, Shimizu et al 2009a. Local injection of nesfatin-1 into the median NTS increased both blood pressure and heart rate (Mimee et al 2012). In contrast, site-specific injection into the nucleus ambiguus, a key site for parasympathetic cardiac control (Mendelowitz 1999), induced bradycardia, although MAP was not affected (Brailoiu et al 2013).…”
Section: Cardiovascular Actionsmentioning
confidence: 93%
“…Electrophysiological studies have identified the median NTS as a potential site through which nesfatin-1 exerts is cardiovascular actions (Mimee et al 2012). Nucb2 mRNA and NUCB2/nesfatin-1 protein expression was observed in this nucleus (Brailoiu et al 2007, Foo et al 2008 and both central nervous and peripheral administration of nesfatin-1 induce c-fos expression in its neurons (Maejima et al 2009, Shimizu et al 2009a.…”
Section: Cardiovascular Actionsmentioning
confidence: 99%
“…Several interactions have been described to underlie the central anorexic effect of nesfatin-1 (Shimizu et al, 2009c). It has also been shown to play important roles in the control of cardiovascular function (Mimee et al, 2012). In situ hybridization and immunohistochemical researches have evidentiated the expression of nesfatin-1 throughout the brain and, particularly, in the medullary autonomic gateway known as the nucleus of the solitary tract (NTS) (Mimee et al, 2012).…”
Section: Nesfatin-1/nucb-2 and Anorexigenic Effectmentioning
confidence: 99%
“…In situ hybridization and immunohistochemical researches have evidentiated the expression of nesfatin-1 throughout the brain and, particularly, in the medullary autonomic gateway known as the nucleus of the solitary tract (NTS) (Mimee et al, 2012). Mimee et al (2012) showed that provide critical insight into the circuitry and physiology involved in the profound effects of nesfatin-1 and highlight the NTS as a key structure mediating these autonomic actions.…”
Section: Nesfatin-1/nucb-2 and Anorexigenic Effectmentioning
confidence: 99%